The students’ career choice and job preparedness strategies: A social environmental perspective - Md. Roknuzzaman Siddiky; Shahanaz Akter (International Journal of Evaluation and Research in Education (IJERE), 2021)
The study aimed to investigate the factors determining the students’ career choice and find out their job preparedness strategies. Moreover, the study sought to propose a theory which could explain the students’ career choice from a social environmental perspective. Primary data for this study were collected from 120 students selected from fourteen academic departments of the Noakhali Science and Technology University (NSTU) in Bangladesh based on snow-ball sampling. The study revealed that several factors involving students’ family preferences, teachers’ advice, job prestige, job security, remunerations, scope of promotion, scope of pension, scope of professional development, personal interests, academic majors, educational attainments and career development trainings have significant association with the students’ career decision-making. However, gender and social class did not have significant effects on the students’ career choice. The study proposed a career choice theory which indicates that the students’ career choice and career preferences are not determined by their personal interests alone; rather they are determined by the interplay of several social, cultural and economic forces. The study indicated that the majority of the respondents undertake self-study to pursue their preferred jobs. While career development trainings play an important role in developing the competencies of the students for jobs, a majority of the respondents do not have such trainings. As such, the study suggested that the students of the NSTU should undertake career development courses as a strategy for job preparedness. Finally, the study suggested that the NSTU should set up a career guidance and counseling cell to link their students with the current labor market.